Assessment of Unused Opioids Following Ambulatory Surgery. Issue 6 (June 2020) - Dixit, Anjali A.; Chen, Catherine L.; Inglis-Arkell, Christina; Manuel, Solmaz P.
Background: Surgery is a risk factor for opioid initiation and subsequent abuse. Discharge opioid prescription patterns after surgery are often varied and not evidence based, which may lead to unnecessary prescription of opioids. We aimed to assess opioid prescribing and unused opioid prescriptions in ambulatory surgery patients at our academic hospital. Methods: We conducted a retrospective observational study based on phone survey and electronic medical records. Adult patients who underwent ambulatory surgery at our large, multisite, tertiary-care hospital system were asked whether they were using the opioids that were prescribed at discharge. Our main outcomes were opioid prescription (defined as being prescribed an opioid on discharge) and unused opioid prescription (defined as being prescribed an opioid but not taking any opioids on postoperative day 1). We evaluated predictors of opioid prescription and unused opioid prescription through univariable and multivariable analyses. We also stratified outcomes by surgical service. Results: Of 4248 adult patients who underwent ambulatory surgical procedures, 3279 (77.2%) responded to the survey. Of all responders, 2146 (65.4%) were prescribed postoperative opioids, and 1240 (57.8%) reported not taking them on postoperative day 1. The highest rates of unused opioid prescriptions were for patients whose primary service were orthopedic surgery (65%) and plastic surgery (62%). Discussion: Opioid prescribing and unused opioid prescriptions are prevalent in our hospital's ambulatory surgical population. Patients undergoing selected ambulatory surgical procedures may not require as much opioid as is currently being prescribed.